2016
DOI: 10.1111/idj.12214
|View full text |Cite
|
Sign up to set email alerts
|

Dental amalgam exposure can elevate urinary mercury concentrations in children

Abstract: Amalgam-filled TS was significantly correlated with U-Hg concentrations in children. Therefore, dental amalgam exposure can affect the systemic mercury concentration in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Since 2014, studies on pregnant women and children showed 1) increased mercury in the urine and blood of children and pregnant women with dental amalgam fillings, as expected (Baek et al 2016; Golding et al 2016); 2) no statistically significant association between maternal amalgam restorations and stillbirth, after accounting for maternal parameters such as age and smoking, among others (Lygre et al 2016); 3) higher maternal and cord blood in mothers with amalgam restorations but no difference in birth weight, length, or head circumference (Bedir Findik et al 2016); and 4) no increased risk of child mortality or neurologic disorders of the sons of female dental staff (Naimi-Akbar et al 2014; Vähäsarja et al 2016).…”
Section: Position Statement On the Safety Of Dental Amalgammentioning
confidence: 54%
“…Since 2014, studies on pregnant women and children showed 1) increased mercury in the urine and blood of children and pregnant women with dental amalgam fillings, as expected (Baek et al 2016; Golding et al 2016); 2) no statistically significant association between maternal amalgam restorations and stillbirth, after accounting for maternal parameters such as age and smoking, among others (Lygre et al 2016); 3) higher maternal and cord blood in mothers with amalgam restorations but no difference in birth weight, length, or head circumference (Bedir Findik et al 2016); and 4) no increased risk of child mortality or neurologic disorders of the sons of female dental staff (Naimi-Akbar et al 2014; Vähäsarja et al 2016).…”
Section: Position Statement On the Safety Of Dental Amalgammentioning
confidence: 54%
“…The Hg levels in the breath [28], blood [21], urine [29], and brain tissue [23] of persons with amalgam restoration were shown to be significantly higher than those in persons who do not have amalgam restoration. The Hg elution mechanism from amalgam restoration is completely unknown, but contributions by aspect metamorphoses (e.g., Ag 2 Hg 3 (γ 1 ) → AgHg(β)) and corrosion (M 1 Hg m → 1M n+ + mHg o + 1ne − ) have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been studies carried out on pregnant women and their children. These have shown that dental amalgam fillings cause increased levels of mercury in the blood and urine of both the children and their mothers [36][37][38] . Findings from a study of the relationship between the presence of amalgam restorations in the mothers and stillbirth showed no statistically significant association 39 .…”
Section: Minamata Conventionmentioning
confidence: 99%